Geochemical Distribution of Copper and Zinc in the Aquatic Sediment of Nyolo Spring Water at Karangploso Malang East Java - Anis Khoirun Nisa; Barlah Rumhayati; Andi Kurniawan (Chemistry Department, The University of Brawijaya, 2019)
Aquatic sediment has a role for heavy metals sink. Understanding the geochemical fractions of heavy metals in the aquatic sediment can predict the mobility and reactivity of heavy metals fractions that can induce environmental problems. The aim of this study was to determine the distribution of geochemical fractions of copper and zinc in aquatic sediment of Nyolo spring. Sediments samples were taken from five locations along the spring. Geochemical fractions of copper and zinc were extracted using BCR (Community Bureau of Reference) sequential extraction method. The concentration of these metals in each extract was analyzed using AAS. The result showed that overall the sediment consisted of zinc at a higher concentration than copper. Amongst the geochemical fractions, copper and zinc were found dominantly at an oxidizable fraction. As the first fraction, Zn was more bioavailable than copper for biological uptake. Furthermore, based on the Risk Assessment Code (RAC) value, the aquatic sediment of Nyolo Spring was low risk to the Zn and Cu contaminations at most sites, except for Zn in Site III showed a medium risk. This metals fraction will potentially available for organism uptake with the changing of pH sediment or overlying water